The impact of the Gwembe Tonga Development Project on the Gwembe people - Musonda, Brenda Lulu (My University, 2009)
ABSTRACT The aim of the study is to investigate the impact of the Gwembe Tonga Development Project (GTDP) on the Gwembe Tonga (GT) people. The GT people were displaced in 1956 to pave way for the construction of the Kariba Dam that would increase the electricity supply to the mines in the Copperbelt and farmers. The number of people displaced was 57, 000 and they were not adequately resettled, rehabilitated and compensated. The GTDP was created in 1996 with the main objective to mitigate the negative impacts that the GT people have endured from the time they were displaced to date. A review of international literature on dams has indicated that dam constructions have led to displacement of the poor and marginalized people. Over 40 million people have been displaced worldwide. As shown in the literature review, are case studies that demonstrate the impacts of dams on people. In this study there six countries that have been listed namely India, China, Lesotho, Togo, Mozambique and Zambia. The people in these countries have experienced similar problems in terms of inadequate compensation, resettlement and rehabilitation. It is also noted that these dams leave a negative impact on the local community and environment. Development projects are equated with a general process of modernization where developed nations’ ways of conducting its affairs have been adopted by the developing countries to boost their economic development. This study has also looked at the developmental theories that the developing countries have adopted for economic transformation of both natural and built environments through construction of projects such as dams, roads, irrigation systems, pipelines, and energy resources, aimed eventually at generating and supporting both agricultural and industrial growth, and with them, increased national incomes. These large-scale development projects frequently make references to benefit the general population but experience has shown that the social costs of these projects are often borne by the indigent rural communities.
Keywords: Gwembe Tonga people; Gwembe Tonga Development Project (GTDP); Dams; Displacement; impact